Strategi Optimalisasi Perencanaan Pembangunan Daerah Berbasis Data Terintegrasi di Kabupaten Lahat - Samsul Hadi (Journal of Research and Development on Public Policy, 2026)
Data-driven regional development planning is a fundamental prerequisite for achieving effective, accountable, and evidence-based public policies. However, the implementation of Indonesia's One Data Policy at the local government level continues to face challenges, particularly regarding the quality, validity, and integration of sectoral data across Regional Government Organizations (Organisasi Perangkat Daerah/OPDs). This study aims to formulate a strategy for optimizing data-integrated regional development planning in Lahat Regency. A qualitative descriptive approach was employed, utilizing observation, in-depth interviews, document analysis, and literature review as data collection techniques. Data were analyzed using the Urgency, Seriousness, and Growth (USG) method to determine priority issues, a fishbone diagram to identify root causes, and policy alternative analysis based on technical, administrative, political, and sustainability criteria. The findings reveal that poor data quality, limited validity, and inadequate integration of sectoral data constitute the primary issues affecting the quality of development planning documents, the accuracy of development program targeting, and evidence-based decision-making. The study recommends a Regulatory-Driven Interoperability strategy through strengthening data standards and metadata regulations, enhancing institutional data governance, and improving information system interoperability. This strategy is expected to strengthen the implementation of Indonesia's One Data Policy and support integrated, adaptive, and sustainable regional development planning. Keywords: One Data Indonesia, data governance, interoperability, regional development.